Periprocedural safety and technical outcomes of the new Silk Vista Baby flow diverter for the treatment of intracranial aneurysms: results from a multicenter experience. (9th March 2019) - Martínez-Galdámez, Mario; Biondi, Alessandra; Kalousek, Vladimir; Pereira, Vitor M; Ianucci, Giuseppe; Gentric, Jean-Christophe; Mosimann, Pascal J; Brisbois, Denis; Schob, Stefan; Quäschling, Ulf; Kaesmacher, Johannes; Ognard, Julien; et al.
Abstract : Purpose: The aim of our study was to assess the technical success and the safety of this new low-profile flow diverter Silk Vista Baby (SVB) by evaluating the intraprocedural and periprocedural complication rate. Material/methods: Clinical, procedural, and angiographic data were analyzed. Results: 41 consecutive patients (28 women; age average 50.5 years) with 43 aneurysms were treated with SVB. Aneurysm sizes were classified by their maximum diameter, with an average size of 9.5 mm (range 2–30 mm). Thirty-four cases were unruptured. five aneurysms previously ruptured, had recurrence after the initial coiling. There were two ruptured cases. Aneurysms' locations were: M1 segment (five cases), M2 segment (three cases), M3 segment (one case), middle cerebral artery (MCA) bifurcation (six cases), carotid-T (two cases), anterior communicating artery/A1/A2 (11 cases), pericallosal artery (four cases), supraclinoid ICA (two cases), PCom (one case), V4 segment (three cases), PCA (three cases), SCA (one case), and PICA (one case). We had five intraprocedural complications which resolved without clinical consequences and three events postprocedural events. Initial occlusion rates were: eight aneurysms (18.6%) were completely occluded, five aneurysms (11.6%) showed near-complete occlusion, four cases (9.3%) showed incomplete filling, and 26 cases (60.4%) showed persisting filling. The mRS score at discharge from the hospital did not change from the admission mRS score. Conclusion: Our study demonstrated that the use of the new low-profile flow diverter, SVB device, for the treatment of intracranial aneurysms is feasible and technically safe.